Overcoming the dormance of forest seeds in the Hileia Baiana (Research, Society and Development, 2022)
Hiléia Baiana is located in the Atlantic Forest biome and has high endemism of species and genera in common with the Amazon Forest. As much as it has a rich vegetation, this region has few studies regarding the species that compose it, bringing with it obstacles to the propagation of seeds and plants. The objective of this study was to verify the effectiveness of methods for overcoming dormancy of seeds of the forest species Aegiphila integrifolia, Apeiba tibourbou, Diospyros lasiocalyx and Margaritaria nobilis, evaluating germination performances for the establishment of new protocols for germination tests. The study was carried out in the Seed Analysis Laboratory and in a greenhouse of the Arboretum Program and the following treatments were used in the seeds: (T1) intact seeds; (T2) mechanical scarification with sandpaper nº 80; (T3) thermal scarification with distilled water at 100 ºC and immersion for 24 hours; (T4) immersion in gibberellic acid at 500 mg L-1 for 24 hours; (T5) immersion in PROGIBB solution at 500 mg L-1 for 24 hours; (T6) immersion in distilled water for 24 hours; (T7) mechanical scarification and immersion in distilled water for 24 hours and (T8) immersion in 2% sodium hypochlorite for 2 minutes and immersion in distilled water at 50 °C for 5 minutes. The pre-germination treatments in species of A. integrifolia and M. nobilis were not effective, great contamination for D. lasiocalyx and the thermal scarification treatment was significantly superior to the other treatments for A. tibourbou. In a greenhouse the treatments were not efficient for Apeiba tibourbou and M. nobilis and for D. lasiocalyx the most efficient method to promote seedling emergence is mechanical scarification + distilled water. However, it is still necessary to apply other methods for the germination of the species.